Samfundsforskning og tekst - det skotske tilfælde som metodisk problem - Halkier, Henrik (HERMES - Journal of Language and Communication in Business, 1990)
The present paper explores some possible links between linguistics and social science, departing from an example of textual analysis originating in research in progress. Particular attention is paid to the characteristics of historical textual analysis and to the relationship between social phenomena and the concepts employed by social scientists. It is argued that the presence of common theoretical problems and shared methodologies provides an interesting starting point for future interdisciplinary research and for up-to-date teaching of post-graduate students.